Gene structure and expression of serotonin receptor HTR2C in hypothalamic samples from infanticidal and control sows - Quilter Claire R; Bagga Meenashki; Moinie Ahmad; Junaid Fatima; Sargent Carole A (BMC Neuroscience, 2012)
Abstract Background The serotonin pathways have been implicated in behavioural phenotypes in a number of species, including human, rat, mouse, dog and chicken. Components of the pathways, including the receptors, are major targets for drugs used to treat a variety of physiological and psychiatric conditions in humans. In our previous studies we have identified genetic loci potentially contributing to maternal infanticide in pigs, which includes a locus on the porcine X chromosome long arm. The serotonin receptor HTR2C maps to this region, and is therefore an attractive candidate for further study based on its function and its position in the genome. Results In this paper we describe the structure of the major transcripts produced from the porcine HTR2C locus using cDNA prepared from porcine hypothalamic and pooled total brain samples. We have confirmed conservation of sites altered by RNA editing in other mammalian species, and identified polymorphisms in the gene sequence. Finally, we have analysed expression and editing of HTR2C in hypothalamus samples from infanticidal and control animals. Conclusions The results confirm that although the expression of the long transcriptional variant of HTR2C is raised in infanticidal animals, the overall patterns of editing in the hypothalamus are similar between the two states. Sequences associated with the cDNA and genomic structures of HTR2C reported in this paper are deposited in GenBank under accession numbers FR720593, FR720594 and FR744452.